SUBCLASA 51 – MATEMATICI. CONSTRUCŢIA VEDETELOR DE SUBIECT ŞI A INDICILOR - BOCANCEA, Evelina (BIBLIOPOLIS, 2020)
Analysing the library collection, especially the Mathematics, and the experience in the documents classifying and indexing of other libraries, the author proposes solution and recommandations in the process of subject heading’s creation approved in the Municipal Library B.P. Hasdeu. It is created the list of subject headings which can be used by catalogators and by reference librarians finding the information. The list is avaiable on the library site.